CHA2DS2-VASc and readmission with new-onset atrial fibrillation, atrial flutter, or acute cerebrovascular accident. (15th January 2021) - Rutland, Joshua; Ayoub, Karam; Etaee, Farshid; Ogunbayo, Gbolahan; Darrat, Yousef; Marji, Meera; Masri, Ahmad; Elayi, Claude S.
Abstract: Background: Although risk factors for atrial fibrillation (AF) and atrial flutter (AFL) are known, identifying patients who will develop AF/AFL within the near future remains challenging. We sought to evaluate if the CHA2 DS2 -VASc risk score (CVRS) can identify hospital readmissions with AF, AFL, or acute cerebrovascular accident (CVA) among hospitalized patients without prior history of AF/AFL. Methods: Using the Nationwide Readmission Database, a study cohort included patients without prior AF/AFL or new diagnosis of AF/AFL at the index hospitalization from 2012 to 2014. Patients were stratified based on the CVRS into three groups: Low (CVRS ≤1), Intermediate (CVRS 2–5), and High (CVRS ≥6).The primary outcome of interest was 180-day readmission rate with a primary or secondary diagnosis of AF/AFL. Secondary outcomes of interest were acute CVA and 6-month mortality rate. Results: A total of 17, 820, 640 patients were included in our study. Over a 6-month follow up duration from the index hospitalization, the overall re-admission rate for new onset atrial arrhythmias (AF/AFL) was 3.48% ( n = 620, 986), acute CVA 0.13% ( n = 22, 522), and all-cause mortality 0.31% ( n = 55, 632). When compared to other groups, patients with a higher CVRS were readmitted more frequently for AF/AFL [odds ratio (OR) 2.43; 95% confidence interval (CI) 2.41–2.45, P < .0001), acute CVA (OR 3.96; 95%CI 3.85–4.08, P < .0001), and all-cause mortality (OR 2.19; 95%CI 2.14–2.24, P < .0001). Conclusion: In this large contemporary cohort, a CHADS2VA2SC score ≥ 6 identified patients without known prior atrial arrhythmias at an elevated risk of developing AF/AFL or acute CVA within 6 months of hospitalization. Highlights: Identifying patients who will develop AF/AFL within the near future remains challenging. CHA2 DS2 -VASc risk score can identify hospital readmissions with AF, AFL, or acute CVA. CVRS ≥6 identified patients at an elevated risk of developing AF/AFL or CVA.